Formula SAE car wiring system engine temperature sensor [electronic resource] - 554640 Mohd. Zin Roslan (2010)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2010